BIOMECHANICAL PARAMETERS OF RUNNING TECHNIQUE IN THE DISTANCE OF SPRINTER FINALISTS OF THE WORLD CHAMPIONSHIP - Balandin, S.I.; Balandina, I.Yu.; Zayko, D.S.; Dmitriev, I.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to compare the spatio-temporal, kinematic and angular characteristics of the running technique over the distance of the strongest sprinters in the world at 100 and 200 m. Methods and structure of the study. As a methodological basis for the study, one of the methods of biomechanics, analysis, was adopted. The data of spatio-temporal, kinematic and angular characteristics of distance running, presented in the IAAF biomechanical report of the men's 100 and 200 m finals of the 2017 World Championships in Athletics, were analyzed. Results and conclusions. In the middle of the straight in the 100 m run, the average speed is 11.60 ± 0.06 m/s, in the 200 m run - 10.31 ± 0.09 m/s. The difference in speed is achieved due to the frequency of steps (4.80±0.08 and 4.27±0.05 sh/s, respectively, p≤0.05), since the step length at both distances is identical and equals on average 2 .42 m. A greater frequency of steps per 100 m is achieved due to the shorter time of the reference (0.093±0.002 and 0.103±0.002 s, p≤0.05) and unsupported (0.116±0.002 and 0.132±0.003 s, p≤0.05) periods . When placing the leg on the support, significantly significant differences (p≤0.05) are observed in the angle of the torso, the angle between the thigh of the fly leg and the vertical. When removing the leg from the support, a significantly significant difference (p≤0.05) is observed in the angle of the torso and the angle between the lower leg of the supporting leg and the horizontal line.